Uncomfortable Knowledges and Transformative Learning : Reimagining the Museum in the Art of Gustafsson&Haapoja - Kosonen, Heidi; Turunen, Johanna; Koistinen, Aino-Kaisa (Taylor & Francis, 2024)
Destructive human action is causing interconnected ecological and social challenges on an unprecedented scale. Scholars and artists from varied fields have critically expressed their concern about this in their research and practice. In this article, we interrogate the transformative potential of critically engaged art by analysing the work of the Finnish artist duo Gustafsson&Haapoja, a collaboration between writer Laura Gustafsson and visual artist Terike Haapoja. Gustafsson&Haapoja’s work focuses on the intersecting human exceptionalist, racist, imperialist, patriarchal, and capitalist histories of violence towards nonhuman animals and dehumanised humans. These histories often provoke uncomfortable affects. As such, they can be challenging to confront. To account for this difficulty, we approach Gustafsson&Haapoja’s art through the idea of transformative learning, a process designed to shake established thinking and behavioural patterns. We investigate how Gustafsson&Haapoja’s art—and art more generally—could function as a transformative learning resource and enable sudden ruptures in hegemonic cultural norms, privileges, and power positions. We focus on how transformative learning emerges through central features in Gustafsson&Haapoja’s work: (1) their investigation and reimagination of the museum, an institution historically tied to notions of humanity and human action; and (2) their critical dissection of the complex relationship between Western-centric conceptualisations of humanity and its “others.” The article is based on a theoretical discussion and a qualitative analysis of works, exhibitions, and texts published by Gustafsson&Haapoja’s Museum of Becoming (2020–21) as well as an interview with the artists.
Keywords: taide; oppiminen; museot; kuvataide; nykytaide; taidemuseot; uudistava oppiminen; kolonialismi